Mitochondria DNA Depletion Syndrome in a Infant with Multiple Congenital Malformations, Severe Myopathy, and Prolonged Postoperative Paralysis. (April 2015) - Thomas, Mark; Salpietro, Vincenzo; Canham, Natalie; Ruggieri, Martino; Phadke, Rahul; Kinali, Maria
Mitochondrial DNA depletion syndromes are an important cause of mitochondrial cytopathies in both children and adults. We describe a newborn with multiple congenital malformations including a right aberrant subclavian artery and a trachea-oesophageal fistula in whom mitochondrial depletion syndrome was unmasked by perioperative muscle relaxation. After vecuronium infusion, the infant developed an irreversible postoperative paralysis, leading to death 32 days after surgery. The present case highlights (a) the clinical heterogeneity of mitochondrial depletion syndrome; (b) the importance of rigorous antemortem and postmortem investigations when the cause of a severe myopathy is uncertain; (c) the possible coexistence of mitochondrial depletion syndrome and congenital malformations as a result of a likely abnormal antenatal embryofetal development and (d) the importance of a careful anaesthetic management of children with mitochondrial depletion syndrome, which could be prone to complications related to the possible depressive effects on mitochondrial electron transport chain mediated by some anaesthetic agents.